Полиморфизм гороховой тли (Acyrthosiphon pisi Kalt.) - Таланов, В.П. (Вестник зоологии, 1970)
According to the author's data Acyrthosiphon pisi К a l t. for the forms, des cribed in the literature, have also the following ones: wingled feinale-sexupara and wingled males. These forms appear in the population, lived on pea and winter vetch in autumn period.